2018
DOI: 10.1136/bcr-2017-223641
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of end-stage renal disease with continuous ambulatory peritoneal dialysis in rural Guatemala

Abstract: A 42-year-old indigenous Maya man presented to a non-profit clinic in rural Guatemala with signs, symptoms and laboratory values consistent with uncontrolled diabetes. Despite appropriate treatment, approximately 18 months after presentation, he was found to have irreversible end-stage renal disease (ESRD) of uncertain aetiology. He was referred to the national public nephrology clinic and subsequently initiated home-based continuous ambulatory peritoneal dialysis. With primary care provided by the non-profit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In Guatemalan rural communities, we have observed a wasting phenotype in very poor individuals with diabetes or other chronic illnesses that precedes progressive kidney disease. 48 Some studies have evaluated the association between BMI and progression of CKD. 49 , 50 , 51 , 52 , 53 , 54 Studies from China and Taiwan, for example, have found that low BMI is an independent risk factor for disease progression in individuals with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In Guatemalan rural communities, we have observed a wasting phenotype in very poor individuals with diabetes or other chronic illnesses that precedes progressive kidney disease. 48 Some studies have evaluated the association between BMI and progression of CKD. 49 , 50 , 51 , 52 , 53 , 54 Studies from China and Taiwan, for example, have found that low BMI is an independent risk factor for disease progression in individuals with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…However, our goal was to understand the challenges of providing kidney care to a large number of uninsured adults in Guatemala, and UNAERC is the dominant institution providing such care. Third, while this study did not include patient perspectives, it complements the authors' prior work studying CKD in Guatemala from the perspective of both children and adults [10,25,26,67,68].…”
Section: Discussionmentioning
confidence: 98%
“…First, the institution's budget outlays have not risen in proportion to meet the population-level increase in demand for RRT [24]. Second, UNAERC serves a diverse and impoverished population with socioeconomic, geographic, and linguistic barriers to care [25,26]. Finally, the institution resides in a complex, high-pressure political environment [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Body pain had previously been found to be one of the factors that had a significant impact on the quality of life of dialysis patients (Bipath, Govender, & Viljoen, 2014). Individuals do CAPD four times a day for 3 years, clinically these individuals have more energy, can be ambulated and have gained 10 kg (Moore et al, 2018). One study explained that there was a phase of non-compliance in individuals with PD therapy.…”
Section: Discussionmentioning
confidence: 99%